Ministry of Trade and Industry Decree No. 923 For The Year 2016 Amending Certain Provisions of the Statute of Rules Enforcing the Provisions of the Import and Export Law and The System Of Exported And Imported Commodities Examination And Control Procedures = وزارة التجارة والصناعة قرار رقم 923 لسنة 2016 بتعديل بعض أحكام لائحة القواعد المنفذة لأحكام قانون الاستيراد والتصدير ونظام إجراءات فحص ورقابة السلع المستوردة والمصدرة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic